"y^{(3)}-27y=e^{3x}+e^{-3x}"
First we solve the homogenous equation "y^{(3)}-27y=0"
The characterisic equation is "\\lambda^3-27=0", which has roots "\\lambda_1=3, \\lambda_2=3e^\\frac{2i\\pi}{3}=-\\frac{3}{2}+\\frac{3\\sqrt{3}}{2}i, \\lambda_3=3e^\\frac{-2i\\pi}{3}=-\\frac{3}{2}-\\frac{3\\sqrt{3}}{2}i"
So the solution of "y^{(3)}-27y=0" is "y=Ae^{3x}+Be^{-\\frac{3}{2}x}\\cos\\frac{3\\sqrt{3}}{2}x+Ce^{-\\frac{3}{2}x}\\sin\\frac{3\\sqrt{3}}{2}x"
Now we find partial solution of "y^{(3)}-27y=e^{3x}+e^{-3x}" in form "y=Vxe^{3x}+We^{-3x}"
By the General Leibniz rule we have "(xe^{3x})^{(3)}=x^{(3)}e^{3x}+3x''(e^{3x})'+3x'(e^{3x})''+x(e^{3x})^{(3)}="
"=0+0+3\\cdot 9e^{3x}+27xe^{3x}=27e^{3x}+27xe^{3x}"
So "y^{(3)}-27y=27Ve^{3x}+27Vxe^{3x}-27We^{-3x}-"
"-27Vxe^{3x}-27We^{-3x}=27Ve^{3x}-54We^{-3x}"
Then "27V=-54W=1", that is "V=\\frac{1}{27},W=-\\frac{1}{54}"
We obtain the general solution "y=Ae^{3x}+Be^{-\\frac{3}{2}x}\\cos\\frac{3\\sqrt{3}}{2}x+Ce^{-\\frac{3}{2}x}\\sin\\frac{3\\sqrt{3}}{2}x+"
"+\\frac{1}{27}xe^{3x}-\\frac{1}{54}e^{-3x}"
Answer: "Ae^{3x}+Be^{-\\frac{3}{2}x}\\cos\\frac{3\\sqrt{3}}{2}x+Ce^{-\\frac{3}{2}x}\\sin\\frac{3\\sqrt{3}}{2}x+"
"+\\frac{1}{27}xe^{3x}-\\frac{1}{54}e^{-3x}"
Comments
Leave a comment